Students' perceptions of service quality in higher education - Nadiri, Halil; Kandampully, Jay; Hussain, Kashif (Routledge Journals, Taylor & Francis Ltd, 2009)
This study aims to diagnose the applicability of the perceived service quality measurement scale to students; and to diagnose the student satisfaction level in higher education. It attempts to diagnose the perceived service quality of administrative units such as services provided by the registrar, library, faculty/school offices, rector office, dormitories, sports and health centre. Descriptive and causal analysis is employed. Reliability and dimensionality of the scale is tested. Results indicate that the nature of perceived service quality measurement instrument is found to be two-dimensional: tangibles and intangibles for higher education services. The results and implications are discussed in detail.
Keywords: perceived service quality; student satisfaction; higher education